Critical population status of the jaguar panthera onca in the Argentine Chaco: camera-trap surveys suggest recent collapse and imminent regional extinction - Quiroga, Verónica Andrea (2013)
The population of jaguars in the semi-arid Chaco is the least well-known in Argentina. Its status in the region is described only from interviews confirming presence through 2003. To update distribution and population density information for the Chaco region, we undertook three camera trap surveys, combined with searches for sign at sites across latitudinal and protection gradients and 156 interviews with local inhabitants across three larger areas. The sites for camera trap surveys were located in areas with the highest density of records in the Argentine Chaco: Copo National Park (1204 trap-days, 24 stations, 344 km of transects); Aborigen Reserve (1993 trap-days, 30 stations, 251 km of transects); El Cantor (2129 trap-days, 35 stations, 297 km of transects). We did not record a single camera trap photograph of jaguars. We recorded very few jaguar tracks and only in the Aborigen Reserve (n=3) and El Cantor (n=1). The map of distribution points confirmed through interviews suggests that the jaguar range has not changed significantly in the past 10 years, however, the camera trap and sign surveys suggest that densities are extremely low. Before our study, the Chaco population was thought to be the largest in Argentina. This perception was wrong: the Chaco jaguar population is the most threatened in the country. In order to determine the status of endangered species, systematic and intensive studies are essential to provide the information necessary for decision-making to manage and conserve these species.